2017
DOI: 10.1111/ijlh.12757
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease in multiple myeloma: Benefits of flow cytometry

Abstract: Over the last 20 years, the approaches to the treatment of multiple myeloma (MM) have changed considerably, which led to an increase in remission rate. Using new diagnostic methods has made it possible to assess the response to treatment more reliably and forecast disease recurrence: allele-specific polymerase chain reaction, new-generation sequencing and multicolor flow cytometry enable minimal residual disease (MRD) detection of with sensitivity of 10 −5 to 10 −6. MRD assessment with flow cytometry using is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…However, it would be most valuable to PCs and CD27, CD19 and CD56 to distinguish between normal and abnormal PCs according to existing literature (Alaterre et al, 2018;Flores-Montero et al, 2016;Tarín et al, 2019). This abnormal phenotype of BM plasma cells has been used to study minimal residual disease in MM, and it has been shown that the persistence of abnormal immunophenotype PC in BM after treatment is associated with poor clinical outcomes (Davies et al, 2002;Galtseva et al, 2018). The results showed that the BMPCs detected by MFC was an attractive companion assessment to morphologic evaluation of a BM smear' furthermore it is a readily available and highly sensitive method to identify and quantify malignant PCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it would be most valuable to PCs and CD27, CD19 and CD56 to distinguish between normal and abnormal PCs according to existing literature (Alaterre et al, 2018;Flores-Montero et al, 2016;Tarín et al, 2019). This abnormal phenotype of BM plasma cells has been used to study minimal residual disease in MM, and it has been shown that the persistence of abnormal immunophenotype PC in BM after treatment is associated with poor clinical outcomes (Davies et al, 2002;Galtseva et al, 2018). The results showed that the BMPCs detected by MFC was an attractive companion assessment to morphologic evaluation of a BM smear' furthermore it is a readily available and highly sensitive method to identify and quantify malignant PCs.…”
Section: Discussionmentioning
confidence: 99%
“…For proper response assessment, the detection of residual cancer cells in the BM (measurable residual disease [MRD]) is crucial [3, 4]. Upon diagnosis, myeloma cells can be identified by flow cytometry according to their high CD138 and CD38 expression, often increased CD56, CD20, or CD117 level compared to the normal plasma cells, and loss of CD45 or CD81 in most cases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Minimal residual disease (MRD) assessment is a powerful prognostic tool and an essential part of patient management for a number of hematologic malignancies (Galtseva, Davydova, Kapranov, Julhakyan, & Mendeleeva, 2018;Paiva, Puig, Cedena, et al, 2020;Paiva, van Dongen, & Orfao, 2015;Paiva, Vidriales, Cervero, et al, 2008;Rawstron, Bottcher, Letestu, et al, 2013;Roshal, 2018;Schuurhuis, Heuser, Freeman, et al, 2018;Theunissen, Mejstrikova, Sedek, et al, 2017). With novel therapies resulting in more frequent deeper responses, the number of patients achieving longer remissions and improved overall survival continues to increase (Galtseva et al, 2018;Rawstron et al, 2013). The need for highly sensitive laboratory assays for assessment of MRD has evolved as a central component of patient monitoring, prognosis, and ongoing care.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-parametric flow cytometry (MFC) is a timely, relatively cost effective, and sensitive method for assessment of MRD (Jelinek, Bezdekova, Zatopkova, et al, 2017;O'Donnell, Ernst, & Hingorani, 2013). With continued improvements in diagnostic performance, highly sensitive MFC (10 −5 to 10 −6 ) is rapidly transitioning from research to routine clinical care (Galtseva et al, 2018;Jelinek et al, 2017;Kumar et al, 2016;Paiva et al, 2008;Paiva et al, 2015;Paiva et al, 2020;Rawstron et al, 2013;Roshal, 2018;Schuurhuis et al, 2018;Theunissen et al, 2017). However, implementing recent advances in MFC MRD assessment presents economic and technical challenges for diagnostic laboratories.…”
Section: Introductionmentioning
confidence: 99%